Heterotopic pregnancy in HIV women. (22nd November 2016) - Savasi, Valeria; Antonazzo, Patrizio; Personeni, Carlo
Heterotopic pregnancy occurs when intrauterine and ectopic pregnancy are concomitant; overall rate rises from 1/30.000 to 1.5/1000 in assisted reproductive technology pregnancies. HIV (human immunodeficiency virus) patients are at increased risk of heterotopic pregnancies due to the greater frequency of assisted reproductive technology and pelvic inflammatory disease. We report the first case of heterotopic pregnancy in HIV woman.